2002
DOI: 10.1016/s0960-9822(02)00815-1
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for CCA1 and LHY in Maintaining Circadian Rhythmicity in Arabidopsis

Abstract: Circadian clocks are autoregulatory, endogenous mechanisms that allow organisms, from bacteria to humans, to advantageously time a wide range of activities within 24-hr environmental cycles. CIRCADIAN CLOCK ASSOCIATED 1 (CCA1) and LATE ELONGATED HYPOCOTYL (LHY) are thought to be important components of the circadian clock in the model plant Arabidopsis. The similar circadian phenotypes of lines overexpressing either CCA1 or LHY have suggested that the functions of these two transcription factors are largely ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
237
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(259 citation statements)
references
References 15 publications
19
237
0
3
Order By: Relevance
“…Alternatively, CCA1 and LHY may have similar functions, but either the dosage of their combined gene products or the interactions between them are crucial for their function. cca1 and lhy single mutants have similar phenotypes (Green and Tobin, 1999;Alabadí et al, 2002;Mizoguchi et al, 2002), and overexpression of each gene has similar effects on circadian rhythms (Schaffer et al, 1998;Wang and Tobin, 1998). Together with the evidence presented here that CCA1 and LHY have similar expression patterns (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Alternatively, CCA1 and LHY may have similar functions, but either the dosage of their combined gene products or the interactions between them are crucial for their function. cca1 and lhy single mutants have similar phenotypes (Green and Tobin, 1999;Alabadí et al, 2002;Mizoguchi et al, 2002), and overexpression of each gene has similar effects on circadian rhythms (Schaffer et al, 1998;Wang and Tobin, 1998). Together with the evidence presented here that CCA1 and LHY have similar expression patterns (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…A cca1 lhy Double Mutant Has More Severe Phenotypes Than a cca1 Single Mutant cca1 and lhy single loss-of-function mutants confer short periods (Green and Tobin, 1999;Alabadí et al, 2002;Mizoguchi et al, 2002) and an initial study showed that a cca1 lhy double loss-of-function mutant (cca1-1 lhy-11) is unable to maintain rhythms of clockcontrolled RNAs for more than a few cycles under constant light (LL; Alabadí et al, 2002;Mizoguchi et al, 2002). However, the lhy allele used in that study was not truly null, because a truncated LHY protein is still expressed (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…normal clock function is important for the timing of onset of starch degradation in continuous light, we compared starch accumulation patterns following transfer to continuous light in wild-type plants and clock mutants. The clock mutants were the short-period mutant cca1 lhy (Alabadí et al, 2002;Mizoguchi et al, 2002) and the long-period mutant prr7 prr9 (Farré et al, 2005;Salomé and McClung, 2005). These mutants are in the Ws-2 and Col-0 backgrounds, respectively.…”
Section: The Onset Of Starch Degradation In Continuous Light Is Influmentioning
confidence: 99%
“…15,16 Conversely, the accumulation of TOC1 in the evening was initially thought to activate CCA1/LHY through an unknown mechanism. 17,18 This central loop interlocks with the "morning" and "evening" loops, forming the basic architecture of the plant circadian clock. In the morning-phased loop, CCA1 and LHY expression increases the expression of PSEUDO-RESPONSE REGULATOR 7 (PRR7), PSEUDO-RESPONSE REGULATOR 9 (PRR9) and PSEUDO-RESPONSE REGULATOR 5/NIGHT INHIBITOR (PRR5/ NI); PRR5/NI, PRR7 and PRR9 subsequently downregulate the expression of CCA1 and LHY by binding to their promoters.…”
Section: Repressive Activity Of Toc1 In Regulating the Clockmentioning
confidence: 99%